Long-term complete remission with ipilimumab in metastatic castrate-resistant prostate cancer: case report of two patients. Issue 1 (18th April 2017) - Cabel, Luc; Loir, Elika; Gravis, Gwenaelle; Lavaud, Pernelle; Massard, Christophe; Albiges, Laurence; Baciarello, Giulia; Loriot, Yohann; Fizazi, Karim
Abstract : Background: Prostate cancer is one of the most common cancers in men and the fourth leading cause of cancer mortality worldwide. Although major progress has been achieved in the last years for patients with metastatic castrate-resistant prostate cancer (mCRPC), thanks to next-generation androgen receptor axis targeted drugs, taxanes, and bone-targeted agents, immunotherapy has not been widely approved and used for the treatment of prostate cancer. Two large studies with ipilimumab, an anti-CTLA-4 (cytotoxic T-lymphocyte antigen 4) antibody reported improved progression-free survival, but not statistically improved overall survival at the primary analysis (CA184 043 and CA184 095). Case presentation: Here, we report on two patients who received ipilimumab in these trials and are still in long-term complete remission with a follow-up of 64 and 52 months respectively after the initiation of ipilimumab. Immunohistochemical staining for hMLH1, hMSH2, hMSH6 and PMS2 was performed on archival prostate biopsy samples from one of the two patients; they exhibited normal protein expression. Interestingly for this patient, a high CD3+ and CD8+ T cell infiltration was observed on archival prostate biopsies as well as Treg FoxP3+ T cells. Conclusion: Ipilimumab produces clinical activity in patients with CRPC, including very long responders with no detectable residual disease.